MR Evaluation of an Unusual Intruder of the Bladder: A Bladder Fibroid Case Report - Chin, Zong Yi; Thian, Yee Liang; Lim, Yi Ting (Current Medical Imaging, 2024)
IntroductionMesenchymal tumours of the bladder are benign but rare occurrences and represent approximately 1% of all bladder tumours.Case ReportWe report a case of a large bladder leiomyoma in an asymptomatic patient. A large pelvic mass was discovered incidentally on the bedside ultrasound scan during a review at the gynecology clinic. Intra-operatively, no mass was seen in the pelvis, and cystoscopy demonstrated an intravesical mass. It was further evaluated with cystoscopy. MR imaging demonstrated typical features of a bladder leiomyoma. Subsequently, the patient underwent partial cystectomy, and the mass was removed, which was histologically proven leiomyoma.ConclusionAwareness of this rare clinical entity and identification of its typical radiological features on MR imaging can aid with accurate diagnosis and preclude unnecessary radical surgery.
Keywords: Urinary bladder